Low power and high speed GDI based convolution using Vedic multiplier - Priyanka, C; Manoj Kumar, N; Sai Priya, L; Vaishnavi, B; Rama Krishna, M (International Journal of Engineering and Technology, 2018)
Convolution is having extensive area of application in Digital Signal Processing. Convolution supports to evaluate the output of a system with arbitrary input, with information of impulse response of the system.Â Linear systems features are totally stated by the systems impulse response, as ruled by the mathematics of convolution. Primary necessity of any application to work fast is that rise in the speed of their basic building block. Multiplier, adder is said to be the important building blocks in the process of convolution. As these blocks consumes plentiful time to obtain the response of the system.Â Several methods are designed to progress the speed of the Multiplier and adder, among all GDI (Gate Diffusion Input) is under emphasis because of faster working and low power consumption. In this paper GDI based convolution is implemented using Vedic multiplier and adder in T-SPICE Software which increases the speed and consumes less power compared to CMOS technology.Â